Vibration characteristic responses due to transient mass loading on wind turbine blades - Al-Hadad, Mohammed; McKee, Kristoffer; Howard, Ian (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Crown Copyright © 2019 Published by Elsevier Ltd.